Structurally colored protease responsive nanoparticle hydrogels with degradation-directed assembly. Issue 38 (25th September 2019) - Torres, Leopoldo; Daristotle, John L.; Ayyub, Omar B.; Bellato Meinhardt, Bianca M.; Garimella, Havisha; Margaronis, Artemis; Seifert, Soenke; Bedford, Nicholas M.; Woehl, Taylor J.; Kofinas, Peter
Abstract : Nanoparticle hydrogels undergo a degradation-directed assembly producing tunable structural color changes for potential sensor applications. Abstract : A tunable protease responsive nanoparticle hydrogel (PRNH) that demonstrates large non-iridescent color changes due to a degradation-directed assembly of nanoparticles is reported. Structurally colored composites are fabricated with silica particles, 4-arm poly(ethylene glycol) norbornene (4PEGN), and a proteolytically degradable peptide. When placed in a protease solution, the peptide crosslinks degrade causing electrostatic binding and adsorption of the polymer to the particle surface which leads to the assembly of particles into compact amorphous arrays with structural color. The particle surface charge and size is investigated to probe their effect on the assembly mechanism. Interestingly, only PRNHs with highly negative particle surface charge exhibit color changes after degradation. Ultra-small angle X-ray scattering revealed that the particles become coated in polymer after degradation, producing a material with less order compared to the initial state. Altering the particle diameter modulates the composites' color, and all sizes investigated (178–297 nm) undergo the degradation-directed assembly. Varying the amount of 4PEGN adjusts the swollen PRNH color and has no effect on the degradation-directed assembly. Taken together, the effects of surface charge, particle size, and polymer concentration allow for the formulation of new design rules for fabricating tunable PRNHs that display vivid changes in structural color upon degradation.